Logos Circulation Conversion as a cyclic renewal of meanings - Lidin, Konstantin (project baikal, 2018)
The term ‘conversion’ is used in different fields of science and practice. It commonly means rethinking, renewing of the meaning of something. The emotional content is regarded as a basic meaning of architectural works. The article shows the connection between emotions and characteristics of informational flows in the society. The parameters of the movement of information in the society (and, as a consequence, the dominant groups of emotions) naturally change over time. The changes are cyclic. Consequently, the dominant type of emotions (style, fashion) cyclically defines the currently dominant meaning of architecture.